BTB Hardware Enterprise : Lorries Rental Service / Nurul Atikah Mahadzir ... [et al.] - Nurul Atikah, Mahadzir; Nur Syasya, Ahmad Fauzi; Rabiatul Adawiah, Mazni; Siti Nor Iszaty, Muhammad; Nurmaisarah, Khairul Nizam; Azlyza Assyikin, Ahmad Mahmud (2019)
BTB Hardware Enterprise has been registered as our business name that are inspired from the cartoon 'Bob the Builders' which intentionally famous at that time. The services that our company provide are lorries rental services and selling construction materials service. There are numbers of contractors are growing up from the small company to the big company. For the small company whose cannot afford to buy themselves any machineries that is required in the construction project, they can absolutely use our services as we provide many services relate to the construction. Our company also provide a special discount to the regular customer like 5% of promotion and others. This company is located at No 32, Taman Baru, Seberang Perai, 13700 Permatang Pauh, Pulau Pinang. As stated above, Pulau Pinang is a developing state which may help our company grow bigger day by day. The main target for our business is contractor, suppliers and residents around Pulau Pinang. To ensure this business run smoothly, all partner members work together to achieve a good business in the future. This business is based on partnerships. The main activities this business is rental and sell services. Everyone in this company has their own capabilities and responsibilities on their position in this company. Our company did a lot of imitative such as promotions and others to attcact the customer to our shop. We expect our business will be more advanced in the future.